Codification of economic legislation in the eradication of Chornobyl accident consequences - Малишева, М. Х. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
The article deals with the matter of economic legislation codification in the sphere of Chernobyl nuclearpower plant consequences, its implementation mechanism and its components. There has been done a studyof modern scientific views on the codification definition as a systematization process. There are disclosed thekey components of codification techniques. There are also proven the features of the procedure and results ofeconomic legislation codification in the sphere of Chernobyl nuclear power plant consequences.